Impact of high-density lipoprotein 3 cholesterol subfraction on periprocedural myocardial injury in patients who underwent elective percutaneous coronary intervention - Kazuhiro Harada (Lipids in Health and Disease, 2018)
Abstract Background Periprocedural myocardial injury (PMI) is a major complication of percutaneous coronary intervention (PCI) and is associated with atherosclerotic coronary plaque and worse clinical outcomes. High-density lipoprotein cholesterol (HDL-C) is a protective factor for cardiovascular disease. However, the role of HDL-C subfractions, such as HDL2 cholesterol (HDL2-C) or HDL3 cholesterol (HDL3-C), in cardiovascular disease remains unclear. The purpose of the study was to investigate the relationship between HDL2-C and HDL3-C subfractions and the incidence of PMI in patients who underwent elective PCI. Methods We enrolled 129 patients who underwent elective PCI for stable angina pectoris. PMI was defined as an increase in high-sensitivity troponin T levels > 5 times the upper normal limit (> 0.070 ng/mL) at 24 h after PCI. Serum HDL-C subfractions (HDL2-C and HDL3-C) were assessed using ultracentrifugation in patients with and those without PMI. Results HDL3-C levels were significantly lower in patients with PMI than in those without (15.1 ± 3.0 mg/dL vs. 16.4 ± 2.9 mg/dL, p = 0.016) and had an independent and inverse association with PMI (odds ratio, 0.86; 95% confidence interval, 0.74–0.99; p = 0.038). When divided by the cut-off value of HDL3-C for PMI (14.3 mg/dL), the incidence of PMI was significantly higher in low HDL3-C patients than in high HDL3-C patients (51.2% vs. 30.2%, p = 0.020). Conclusions HDL3-C was an independent inverse predictor of PMI in patients who underwent elective PCI.